The bond between intelligences: Cultural, emotional, and social - Kumar, Naresh; Che Rose, Raduan; Sri Ramalu, Subramaniam (International Society for Performace Improvement, 2008)
Increasing interest in multiple forms of nonacademic intelligences in addition to the wellestablished intelligent quotient (IQ) to explain individual success has triggered a need for clear establishment of the theoretical and empirical connection among these constructs. As such, this article explores the interrelationship that exists among three forms of nonacademic intelligences: ultural, emotional, and social. Theoretical and practical implications are also discussed.